Drugs
The book gives a non-technical account of how drugs work in the body. The twentieth century saw a remarkable upsurge of research on drugs, with major advances in the treatment of bacterial and viral infections, heart disease, stomac ulcers, cancer, and metal illnesses. These, along with the introduction of the oral contraceptive, have altered all of our lives. There has also been an increase in the recreational use and abuse of drugs in the Western world. The book reviews both legal (alcohol, nicotine, and caffeine) and illegal drugs and disscusses current idea about why some are addictive, and whether drug laws need reform.